Composition and Radical Scavenging Activity of Edible Wild Pulicaria jaubertii (Asteraceae) Volatile Oil - Hussein, Khaled; Ahmed, Ahlam H.; Al-Maqtari, Maher A. (PSM Biological Research, 2017)
The objectives of this work were to determine chemical composition and evaluate the radical scavenging activity (RSA) of P. jaubertii volatile oil from outskirts of Sana’a city (PjSO), as well as RSA of P. jaubertii volatile oil from Hajja Province (PjHP), Yemen. The composition of PjSO volatile oil was described by infra-red (IR) spectroscopy and gas chromatography/mass spectrometry (GC/MS). RSA of investigated oils were estimated, using spectrophotometric DPPH (2.2`-diphenyl-1-picrylhydrazyl) method. A total of sixteen components, which represent 99.98% of the total composition of PjSO oil, were identified. GC/MS analysis showed that the dominant component of PjOS oil is carvotanacetone (98.34%). The carbonyl group of carvotanacetone was identified from the IR spectrum by the appearance of absorption band at 1700 cm-1. The obtained analytical data showed that the PjSO essential oil possess 1.3% (v/w) oil content. This indicated that the PjSO essential oil has a commercial potential for production of carvotanacetone. Furthermore, RSA results indicated that PjSO essential oil has a higher RSA in comparison with that of PjHP oil and slightly higher than that of ascorbic acid at higher concentrations. Our finding reveals that PjSO oil could serve as safe natural alternative for synthetic antioxidants in food and pharmaceutical industries.